Pengaruh Sales Promotion, Hedonic Shopping Motivation Dan Shopping Lifestyle Terhadap Impulse Buying Pada Pelanggan E-Commerce Shopee Di Kecamatan Medan Sunggal - Prity Arlia Putri; Wan Suryani; Lailan Tawila Berampu (Universitas Medan Area, 2023)
The purpose of this study was to determine and analyze the influence of Sales Promotion, Hedonic Shopping Motivation and Shopping Lifestyle on Impulse Buying on Shopee E-Commerce Customers in Medan Sunggal District. The research model used is associative research, where the variables are measured using a Likert scale. The data collection method is carried out using a questionnaire with a list of questions or questionnaires that have been prepared in advance and given to respondents. The population in this study is Shopee E-commerce customers in Medan Sunggal District, Kampung Lalang, Medan City, totaling 133,939 respondents. Because of the large population, the authors took 1 Kelurahan, namely Kelurahan Lalang, which amounted to 21,268 respondents. The sampling method using the Slovin method in this study, the sample obtained was 100 respondents. Data processing using SPSS Version 22 software, with descriptive analysis and multiple regression analysis hypothesis testing. The results of the study show that (1) partially Sales Promotion affects Impulse Buying (2) partially Hedonic Shopping Motivation affects Impulse Buying (3) Partially Shopping Lifestyle variables affect Impulse Buying (4) Simultaneously there is a positive and significant influence between Sales Promotion, Hedonic Shopping Motivation and Shopping Lifestyle on Impulse Buying on Shopee E-Commerce Customers in Medan Sunggal District.